Research on the effect of super high frequency field on green tea extraction and extract quality - Rubanka, Kateryna; Bessarab, Alexander; Terletska, Vita (My University, 2020)
The article characterises non-brick green tea as a product of mass consumption. It has been described how practical it is to produce liquid extracts based on it and use them further in the non alcoholic drinks technology. Achieving high yields of extractives from tea requires intensification of the mass transfer process. The analysis of scientific sources has shown that pre-treatment of raw materials is one of the most promising methods for this purpose. The article presents comparative characteristics of green tea extracts obtained using pre treatment in the super high frequency field and of ones produced without it. The optimal power of the super high frequency field for extracts heated up to 60°С has been selected and analysed. If the energy of super high frequency is applied to a fresh mixture of tea and an extractant, with its further extraction in a rotary extractor IKA-RV-10 at the dilution 280 mBr, the yield of extractives doubles. The action of the microwave field leads to a 40% increase in the content of extractives in the resulting extract: the yield of phenolic substances increases by 44%, of caffeine by 45%, of substances with vitamin P activity by 23%, compared with the extracts produced without additional treatment. However, the chlorophyll and aldehyde content decreases. Pre-treatment with super high frequency energy in the course of green tea extraction helps effectively extract phenolic compounds like catechins that affect the taste of final beverages. This technique allows doubling the yield of catechins. Besides, it has been confirmed that the chemical composition (namely the quantity of hydroxyl groups in the catechin structure) determines the intensity of the transition of catechins into the composition of the extract. The findings on the safety of the extracts obtained have allowed establishing that though the contents of mercury, arsenic, lead, copper, and iron increase, they do not exceed the maximum permissible concentrations. This proves the safety of the extracts produced. The research results obtained make it possible to intensify the plant extract production technology without using any special extractors.
Keywords: non-brick green tea; super high frequency field; extract; extraction; catechins; нецегляний зелений чай; екстракція; екстракт; катехіни; надвисокочастотне поле; кафедра технології консервування